2015
DOI: 10.1038/aps.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and structural optimization of 1-phenyl-3-(1-phenylethyl)urea derivatives as novel inhibitors of CRAC channel

Abstract: Aim: Ca 2+ -release-activated Ca 2+ (CRAC) channel, a subfamily of store-operated channels, is formed by calcium release-activated calcium modulator 1 (ORAI1), and gated by stromal interaction molecule 1 (STIM1). CRAC channel may be a novel target for the treatment of immune disorders and allergy. The aim of this study was to identify novel small molecule CRAC channel inhibitors. Methods: HEK293 cells stably co-expressing both ORAI1 and STIM1 were used for high-throughput screening. A hit, 1-phenyl-3-(1-phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…The urea analogue 12 was the most potent of a number of analogues reported 35 as specific inhibitors of Orai1, but was not active in our assay. Finally, the extensively-studied biphenyl analogue Synta66 (13) [36][37][38] has been demonstrated to be a potent (IC 50 26 nM by patch-clamp assay) and selective Orai1 inhibitor.…”
Section: Biologymentioning
confidence: 76%
See 1 more Smart Citation
“…The urea analogue 12 was the most potent of a number of analogues reported 35 as specific inhibitors of Orai1, but was not active in our assay. Finally, the extensively-studied biphenyl analogue Synta66 (13) [36][37][38] has been demonstrated to be a potent (IC 50 26 nM by patch-clamp assay) and selective Orai1 inhibitor.…”
Section: Biologymentioning
confidence: 76%
“…The percentage inhibition of the maximum peak height for each concentration of each compound normalized to its corresponding DMSO control was calculated and plotted separately for peak 1 (a measure of the release of endoplasmic reticulum calcium store) by addition of CPA to assess potential non-specific effects on Ca 2+ homeostasis and peak 2 (a measure of store-operated Ca 2+ influx). 35,54 Where the % inhibition of peak 2 (SOCE) did not exceed 10% at 100 µM in initial assessments, these compounds were defined as not active.…”
Section: Compound Library Developmentmentioning
confidence: 99%
“…Furthermore, this compound could specifically reduce ORAI1/STIM1-mediated Ca 2+ entry, while exhibited no inhibitory effect on other ORAI channels. These results indicated that [128].…”
Section: -Phenyl-3-(1-phenylethyl)urea Derivativesmentioning
confidence: 73%
“…A series of 1-phenyl-3-(1-phenylethyl)urea derivatives has been recently identified as CRAC channel inhibitors. As the lead compound, compound 22 could inhibit Ca 2+ influx with IC 50 of 3.25 ± 0.17 μM in HEK293 cells stably co-expressing ORAI1 and STIM1 [128]. The Ca 2+ influx assay and electrophysiological experiments showed that compound 22 could partially inhibit Ca 2+ entry in constitutively opened CRAC channels which were formed by ORAI1-SS (monomer ORAI1 covalently linked with two S336-485 domains) and completely inhibit the Ca 2+ entry and the current mediated by the opened STIM1free V102A channel (a mutant of ORAI1), which is a constitutively opened CRAC channel, even in the absence of STIM1.…”
Section: -Phenyl-3-(1-phenylethyl)urea Derivativesmentioning
confidence: 99%
See 1 more Smart Citation